Pengaruh Peran Ganda dan Beban Kerja Terhadap Kinerja Pegawai Wanita Dengan Stres Kerja Sebagai Variabel Intervening (Studi Pada Universitas Sultan Ageng Tirtayasa Banten) - Dedeh Komariah; Wawan Prahiawan; Lutfi (Fakultas Ekonomi dan Bisnis Universitas Prima Graha, 2021)
The sustainability of an organization depends on the performance of its employees. On the other hand, women's participation in certain roles often becomes a conflict that makes it difficult to fulfill work and family needs. However, in many jobs, female employees still have to maintain the best working conditions. The purpose of this study is to examine and analyze the elements that influence the performance of female employees with the effectiveness of multiple roles and suitability of workloads through decreasing work stres. This research was conducted at the University of Sultan Ageng Tirtayasa Banten using a descriptive quantitative method using a sample of 130 respondents with an interval scale measurement of 1-10 and analyzed using the Smart PLS 3.29 application. The results of this study state that multiple roles (work family conflict) have a significant effect on the performance of female employees with a coefficient of 16.3%, workload significantly affects the performance of female employees with a coefficient of 23.1%, multiple roles (work family conflict) have a significant effect on stres. work with a coefficient of 21.8%, workload has a significant effect on the work stres of female employees with a coefficient of 47.6% and work stres has a significant effect on the performance of female employees. with a coefficient of 57.8%.